The utility of the creatinine excretion to production ratio and the plasma creatinine and cystatin C based kinetic estimates of glomerular filtration rates in critically ill patients with sepsis - Md Ralib, Azrina; Ramly, Nur Fariza; Nanyan, Suhaila; Mat Nor, Mohd Basri (Wolters Kluwer Health, 2022)
Introduction: Creatinine kinetics denotes that under steady state conditions creatinine production (G) will equal creatinine excretion rate (E). The glomerular filtration (GFR) is impaired when excretion is less than production. The kinetic estimate of GFR (keGFR) was and E/G ratio were proposed as a more accurate estimate of GFR in the acute settings with rapidly changing kidney function. We evaluated keGFR and E/G to diagnose AKI, predict recovery, and predict death or dialysis. Materials and Methods: A prospective observational study of critically ill patients. Inclusion criteria were patients > 18 years old with sepsis, defined as clinical infection with an increase in SOFA score >2 and plasma procalcitonin >0.5ng/ml. Plasma creatinine and Cystatin C were measured on ICU admission and 4 hours later, and their keGFR calculated. Urine creatinine and urine output were measured over 4-hours to calculate the E/G ratio. Results: A total of 70 patients were recruited, of which 49 (70%) had AKI. Of these, 33 recovered within 3 days, and 15 had composite outcome of death or dialysis. Day 1 keGFRCr and keGFRCysC discriminated AKI from non-AKI with AUCs of 0.85 (95% Confidence interval: 0.74 to 0.96), and 0.86 (0.76 to 0.97) respectively. The E/G ratio predicted of AKI recovery (AUC 0.81 (0.69 to 0.97)). The keGFRs were not predictive of death or dialysis, whereas E/G was predictive (AUC of 0.76 (0.63 to 0.89). Conclusion: keGFR was strongly diagnostic of AKI. The E/G ratio predicted AKI recovery and composite outcome of death and dialysis.